Long‐Term Effects of Forest Liming on Soil, Soil Leachate, and Foliage Chemistry in Northern Pennsylvania. Issue 4 (12th June 2015) - Long, Robert P.; Bailey, Scott W.; Horsley, Stephen B.; Hall, Thomas J.; Swistock, Bryan R.; DeWalle, David R.
Abstract : Sugar maple ( Acer saccharum Marsh.) decline disease, decreased growth, and regeneration failure have been related to a low supply of Ca and Mg. There is increased interest in augmenting cation availability via liming, but there is little information on the amounts of lime required and the longevity of the lime treatment. A single application of 22.4 Mg ha ‐1 of dolomitic limestone in 1985 at four forested sites in Potter County, PA has shown that soil, soil water, and sugar maple foliage chemistry are significantly altered by liming and the changes in soils and foliage persist as long as 21‐yr post‐treatment. By 2001, only 3 kg ha ‐1 of lime remained undissolved while increases in exchangeable Ca and Mg, and pH continued through 2006 at depths up to 35 to 45 cm. Exchangeable Mn and Al concentrations were significantly reduced by lime application, though effects were slower to develop at deeper depths. Soil solution chemistry from 1996 was highly variable but reflected the changed soil nutrients. On limed plots, sugar maple foliage had elevated concentrations of Ca and Mg in 2006 samples, indicating the persistence of the lime treatment. Comparison of Ca/Al ratios in soil solution, soils, and foliage show inconsistencies from previous published risk thresholds. Species‐specific thresholds of Ca and Mg availability in soil and foliage have better potential management application and should be more rigorously tested as stress indicators.